Restitusi Bagi Korban Tindak Pidana: Sebuah Tawaran Mekanisme Baru - Marasabessy, Fauzy (Jurnal Hukum & Pembangunan, 2015)
A criminal action may cause harm to others the victims of crime. To obtain such compensation, a victim of a criminal act can be the procedures provided by the Criminal Procedure Code the merger lawsuit for damages. After the enactment of Law No. 13 of 2006 on Witness and Victim Protection, all victims of crime are also given the option to apply for compensation in the form of restitution through the Agency. However, there are some problems that arise in the implementation of mechanisms to obtain restitution for the victims of such crime. The problems are not just about rules, but also the institution that is authorized to assist victims of crime get the right to restitution